Incidence and relative risk of hearing disorders in professional musicians. Issue 7 (30th April 2014) - Schink, Tania; Kreutz, Gunter; Busch, Veronika; Pigeot, Iris; Ahrens, Wolfgang
Abstract : Background: Hearing disorders have been associated with occupational exposure to music. Musicians may benefit from non-amplified and low-intensity music, but may also have high risks of music-induced hearing loss. Aims: To compare the incidence of hearing loss (HL) and its subentities in professional musicians with that in the general population. Methods: We performed a historical cohort study among insurants between 19 and 66 years who were employed subject to social insurance contributions. The study was conducted with data from three German statutory health insurance providers covering the years 2004–2008 with about 7 million insurants. Incidence rates with 95% CIs of HL and the subentities noise-induced hearing loss (NIHL), conductive HL, sensorineural HL, conductive and sensorineural HL, as well as tinnitus were estimated stratified by age, sex and federal state. A Cox regression analysis was conducted to estimate adjusted HRs and two-sided 95% CIs for HL and its subentities. Results: More than 3 million insurants were eligible, of whom 2227 were identified as professional musicians (0.07%). During the 4-year observation period, 283 697cases of HL were seen, 238 of them among professional musicians (0.08%), leading to an unadjusted incidence rate ratio of 1.27. The adjusted hazard ratio of musicians was 1.45 (95% CI 1.28 to 1.65) for HL and 3.61 (95% CI 1.81 to 7.20) for NIHL. Conclusions: Professional musicians have a high risk of contracting hearing disorders. Use of already available prevention measures should reduce the incidence of HL in professional musicians.